2017
DOI: 10.4335/15.3.625-645(2017)
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Authentic Leadership on Psychological Empowerment of the Employees in the Slovenian Local Self-Government Institutions

Abstract: Main aim of our research was to empirically test how the supervisor’s authentic leadership relates to the four independent constructs representing followers’ psychological empowerment in Slovenian local self-government institutions. We tested four hypotheses in one structural model by using structural equation modelling (SEM). The quantitative data for our analysis was collected through a survey on 169 employees of Slovenian municipalities. Findings show that the supervisor’s authentic leadership is positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The results of statistical analysis to answer the first question of the research showed that the authentic leadership variable explains 74.5% of the variance of the psychological empowerment variable. This finding is based on the results of research by Marič et al, and it is consistent with the statement that authentic leadership affects the psychological empowerment of employees in local self-government institutions (Marič et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…The results of statistical analysis to answer the first question of the research showed that the authentic leadership variable explains 74.5% of the variance of the psychological empowerment variable. This finding is based on the results of research by Marič et al, and it is consistent with the statement that authentic leadership affects the psychological empowerment of employees in local self-government institutions (Marič et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Their results found that the direct effect of AL on proactive behaviour was not significant; however, PsyEmp, acting in a mediating role, did have a positive effect on proactive behaviour. Moreover, a study examining each of the four PsyEmp elements found a strong relationship between AL and self-determination, followed closely by impact, while meaning and competence were also positively related, albeit less strongly (Marič et al, 2017). In addition, PsyEmp was found to mediate the impact of AL on creativity in Pakistani nongovernment organisations (Mubarak & Noor, 2018).…”
Section: Relationship Between Authentic Leadership and Job Motivationmentioning
confidence: 95%
“…Thus, according to [13], the motivation for achievement is good both for starting a business and for its long-term success. The motivation for achievement is one of the key entrepreneurial competencies [14][15][16][17].…”
Section: The Need For Achievementmentioning
confidence: 99%